2008
DOI: 10.1007/s10552-008-9280-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of blood-pressure-lowering medication and risk of prostate cancer in the Cancer Prevention Study II Nutrition Cohort

Abstract: These results do not support the hypothesis that anti-hypertensive medication is strongly associated with risk of prostate cancer. Confounding by concurrent illness may explain inverse associations seen in other studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…4,6,13,15,18,[22][23][24]27,31,33 When the analyses were restricted to studies that investigated the effect of only ACE inhibitors on cancer risk, the 12 cohort and nested case-control studies showed a nonsignificant protective effect (RR 0.93, 95% CI 0.86-1.01), 4,12,15,16,19,21,23,29−33 and the 8 studies with longterm follow-up showed a significant protective effect (RR 0.89, 95% CI 0.80-0.98). 4,13,15,18,22,23,31,33 No significant change was observed when we excluded two studies with crude estimates. 11,28 In the subgroup analyses by study design (Figure 2) analysis of the conventional case-control studies (RR 1.14, 95% CI 1.00-1.31).…”
Section: Effect Of Medication Use On Risk Of Cancermentioning
confidence: 99%
“…4,6,13,15,18,[22][23][24]27,31,33 When the analyses were restricted to studies that investigated the effect of only ACE inhibitors on cancer risk, the 12 cohort and nested case-control studies showed a nonsignificant protective effect (RR 0.93, 95% CI 0.86-1.01), 4,12,15,16,19,21,23,29−33 and the 8 studies with longterm follow-up showed a significant protective effect (RR 0.89, 95% CI 0.80-0.98). 4,13,15,18,22,23,31,33 No significant change was observed when we excluded two studies with crude estimates. 11,28 In the subgroup analyses by study design (Figure 2) analysis of the conventional case-control studies (RR 1.14, 95% CI 1.00-1.31).…”
Section: Effect Of Medication Use On Risk Of Cancermentioning
confidence: 99%
“…Less clear is the effect of calcium channel blockers in cancer, particularly prostate cancer. Thus, whereas some investigators report that the use of calcium channel blockers is inversely associated with prostate cancer (Debes et al, 2004), others have failed to find such a relationship (Rodriguez et al, 2009). Thus, it is of interest to investigate the potential effectiveness of these drugs in prostate cancer therapy, especially because both cardiovascular problems and prostate cancer are common in elderly men (Yoshinaga et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the subject, with conflicting results. Positive results are reported for individual drugs, classes of drugs (such as calcium-channel blockers and beta-blockers), and blood pressure medication as a whole, but there are also studies that fail to report such findings [2,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%